2016
DOI: 10.1136/bmjopen-2016-011231
|View full text |Cite|
|
Sign up to set email alerts
|

Out-of-hours antibiotic prescription after screening with C reactive protein: a randomised controlled study

Abstract: ObjectiveTo evaluate the effect of preconsultation C reactive protein (CRP) screening on antibiotic prescribing and referral to hospital in Norwegian primary care settings with low prevalence of serious infections.DesignRandomised controlled observational study at out-of-hours services in Norway.SettingPrimary care.Participants401 children (0–6 years) with fever and/or respiratory symptoms were recruited from 5 different out-of-hours services (including 1 paediatric emergency clinic) in 2013–2015.InterventionD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…After full-text evaluation, 152 publications were relevant for POCT. After excluding 34 publications [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] ( Supplementary Materials ), 13 studies [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] reported across 22 publications [ 61 , 62 , 63 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After full-text evaluation, 152 publications were relevant for POCT. After excluding 34 publications [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] ( Supplementary Materials ), 13 studies [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] reported across 22 publications [ 61 , 62 , 63 …”
Section: Resultsmentioning
confidence: 99%
“…The 13 studies comprised a total of 9844 randomised patients ( Table 1 ); nine individually randomised 4529 patients to intervention groups [ 61 , 63 , 64 , 65 , 68 , 69 , 71 , 72 , 73 ], and four randomised 226 sites and/or 173 physicians with 5315 patients [ 62 , 66 , 67 , 70 ]. Six studies included adult patients only [ 66 , 67 , 68 , 69 , 70 , 73 ], four included children only [ 61 , 62 , 63 , 64 ], two included both adults and children [ 65 , 72 ], and one did not distinguish age groups [ 71 ]. Participants had a mean age of 26.4 (SD 15.0) (range: 0–90) years, and 43.9% were male.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical signs and symptoms of viral RTIs overlap with those of bacterial infections. It is challenging to clinically distinguish bacterial from viral infections and different viral pathogens [7]. This diagnostic uncertainty leads to overprescription of antibiotics and extra diagnostic testing (along with costs) to rule out bacterial infections [8,9].…”
mentioning
confidence: 99%